1979
DOI: 10.1037/0022-3514.37.12.2212
|View full text |Cite
|
Sign up to set email alerts
|

Locus of control, interpersonal trust, and assertive behavior among newlyweds.

Abstract: This study related two cognitive personality characteristics-locus of control and interpersonal trust-to assertive behavior in a sample of recently married couples. Assertive behavior was measured by the Inventory of Marital Conflicts, an observational procedure in which couples resolve disagreements about hypothetical marital problems. Hypotheses were formulated in terms of individual locus of control as well as two combinations of locus of control and interpersonal trust-internal -low trust and external -hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 25 publications
3
23
0
Order By: Relevance
“…For Locus of Control, the results supported findings of earlier research; for example, internal wives and husbands were more proactive in addressing marital conflict (Doherty & Ryder, 1979), and being internal was positively related to marital satisfaction (Bugaighis et al, 1983). The present study extended those findings as Locus of Control correlated positively with all four aspects of intimate relationships and was a significant positive predictor of two (Emotional and Physical).…”
Section: Antecedents Of Relationship Satisfactionsupporting
confidence: 90%
See 1 more Smart Citation
“…For Locus of Control, the results supported findings of earlier research; for example, internal wives and husbands were more proactive in addressing marital conflict (Doherty & Ryder, 1979), and being internal was positively related to marital satisfaction (Bugaighis et al, 1983). The present study extended those findings as Locus of Control correlated positively with all four aspects of intimate relationships and was a significant positive predictor of two (Emotional and Physical).…”
Section: Antecedents Of Relationship Satisfactionsupporting
confidence: 90%
“…One study found external women less likely to take responsibility for marital problems, while attributing the difficulties to external factors (Mlott & Lira, 1977). Alternately, Doherty and Ryder (1979) proposed that internal people are more likely to use social skills to influence their environment, and found internal husbands more proactive in resolving marital conflicts.…”
Section: Interpersonal Trustmentioning
confidence: 96%
“…In general marital literature, studies focusing specifically on locus of control and marriage have hypothesized a positive relationship between internal locus of control and one's satisfaction with the marital partner. This hypothesis is based on the theoretical assumption that those people with internal locus of control are most likely to engage in active efforts to solve their marital problems (Doherty, 1983;Doherty & Ryder, 1979;Sabatelli, 1986).…”
Section: The Conflict Contextmentioning
confidence: 99%
“…In a related study, Doherty and Ryder (1979) investigated the relationship between locus of control and more specific areas of marital functioning: interpersonal trust and assertive behavior. Each couple participated in the Inventory of Marital Conflicts (IMC) (Olson & Ryder, 1970), a laboratory procedure wherein each member of a couple receives selectively slanted versions of the same marital disagreement situation.…”
Section: General Attributional Processes In Nondistressed Couplesmentioning
confidence: 99%